The Effectiveness of Communication Learning Activities Based on Tradisional Game Toward the Cognitive Process Dimension - I Wayan Widiana; I nyoman Jampel; I Gusti Ayu Priyanitha Prawini (LPMPP Universitas Negeri Yogyakarta, 2018)
Abstract:This paper aims to describe the effectiveness of traditional games in improving the cognitive processes of students through communicating activities.This research motivated by the activities of students in the learning process that tend to be passive, so that can have an impact for the the cognitive processes of students.The data that collected in this study is the cognitive process data of IV grade students which is taken by using the essay test which amounted to 17 items According to the basic competencies on the theme of my residence subthema 2 and subtheme 3. The hypothesis was tested by using inferential statistic t test. The results showed that there were significant differences in cognitive processes between groups of students who were educated with learning activities communicating based on traditional games and students taught by conventional learning (t count = 7.50 t table = 2,00).This research has a positive impact to the cognitive processes of students through learning activities to communicate the form of traditional games.Keywords: activities, communication learning,traditional game Efektivitas Aktivitas Pembelajaran Mengomunikasikan Berbasis Permainan Tradisional Terhadap Dimensi Proses KognitifAbstrak: Tulisan ini bertujuan untuk menggambarkan keefektifan permainan tradisional dalam meningkatkan proses kognitif siswa melalui aktivitas mengomunikasikan. Hal ini dilatarbelakangi oleh aktivitas siswa dalam proses pembelajaran yang cenderung pasif sehingga berdampak pada proses kognitif siswa. Data yang dikumpulkan dalam penelitian ini adalah data proses kognitif siswa kelas IV yang diambil dengan menggunakan tes essay yang berjumlah 17 butir sesuai dengan kompetensi dasar pada tema tempat tinggalku subtema 2 dan subtema 3. Hipotesis diuji dengan menggunakan statistik inferensial uji t. Hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan proses kognitif antara kelompok siswa yang dibelajarkan dengan aktivitas pembelajaran mengomunikasikan berbasis permainan tradisional dan siswa yang dibelajarkan dengan pembelajaran konvensional (thitung=7,50 ttabel=2,00). Penelitian ini berpengaruh positif terhadap proses kognitif siswa melalui aktivitas pembelajaran mengomunikasikan berbasis permainan tradisional.Kata Kunci: aktivitas, pembelajaran mengomunikasikan, permainan tradisional